(untitled) (e-Journal of Linguistics, 2019)
The difficulties in knowing and understanding the meaning of a language often appear in units of language with an idiomatic meaning, such as phrasal verb. A single unit of phrasal verb usually produces a meaning which is totally different with the meaning of its constituent. Phrasal verb ‘pick up’ is a unique phrasal verb since it bears various meanings unlike other phrasal verbs. The implementation of Natural Semantic Metalanguage (NSM) as a theory in this study leads to a great significance of avoiding misunderstanding on the meanings of phrasal verb ‘pick up’ by defining the meanings through semantic structures. This study is intended to find and describe the meanings of phrasal verb ‘pick up’. Mention the object of the study here result of this study showed that phrasal verb ‘pick up’ is a kind of transitive phrasal verb which often followed by object. The different objects in phrasal verb ‘pick up’ lead to non- composition polysemi between DO / HAPPEN. This combination of two polysemies come in eight meanings.